Efek Fortifikasi Asam Folat pada Beras Premiks Lokal terhadap Konsentrasi dan Hasil Belajar pada Santri - Aminuddin Syam; Nurpudji Astuti Taslim; Budu Budu; Nurhaedar Jafar; Muhammad Jufri (Media Kesehatan Masyarakat Indonesia, 2019)
Deficiency of iron intake and folic acid intake can cause a shortage of concentration and studentachievement. The purpose of this study explains the effect of giving fortified rice with folic acid on concentrationand Student learning outcome. This study is an experimental using the Double-Blind Randomized ControlTrial Design. The population is students in the Annihaya boarding school is 603 people. The sample is 80male students of aged 12-15 years. The sample was divided into four groups, namely groups given fortificationrice (anemia and non-anemia) and groups given non-fortification rice (anemia and non-anemia). The resultsshowed that the greatest decrease in concentration scores in the intervention group was -2,75, while in thecontrol group, it decreased by -1,65 and there was no significant difference either in the group or the differencegroup with p value> 0,05. The increase in student learning outcomes in the intervention group was 0,11while the control group had decreased by -0,44. The results show that there were significant differences in theintervention group before and after the intervention. But statistical tests showed there were no differences instudent learning outcomes scores between the intervention group and the control group (p>0,05). The conclusionis that the concentration of students decreased in all groups after the intervention and the greatest decreaseoccurred in the group given non-anemic fortified rice. Student learning outcomes increased in all groupsafter the intervention and the largest increase occurred in the anemic group who were given fortified rice.